2018
DOI: 10.1074/jbc.tm117.000233
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective, excited-state quenching mechanisms in diverse photosynthetic organisms

Abstract: Light-harvesting complexes (LHCs) serve a dual role in photosynthesis, depending on the prevailing light conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…The regulation of the XC and mediated NPQ at the molecular level has been the object of intense research in various photosynthetic organisms (see the recent syntheses by Niyogi and Truong , Demmig‐Adams et al. , Goss and Lepetit , Magdaong and Blankenship , Pinnola and Bassi ). In microalgae, its peculiarities have been extensively studied in green representatives (Finazzi and Minagawa , Erickson et al.…”
Section: What Is the Xanthophyll Cycle (Xc)‐related Nonphotochemical mentioning
confidence: 99%
“…The regulation of the XC and mediated NPQ at the molecular level has been the object of intense research in various photosynthetic organisms (see the recent syntheses by Niyogi and Truong , Demmig‐Adams et al. , Goss and Lepetit , Magdaong and Blankenship , Pinnola and Bassi ). In microalgae, its peculiarities have been extensively studied in green representatives (Finazzi and Minagawa , Erickson et al.…”
Section: What Is the Xanthophyll Cycle (Xc)‐related Nonphotochemical mentioning
confidence: 99%
“…Additionally, it was shown that in the presence of high amounts of Ddx cycle pigments, for example, in diatom cells cultivated at higher light intensities, a large part of the total Ddx/Dtx pool is located not only transiently but stable within the lipid phase of the membrane (Lepetit et al, ). However, a part of the total Dtx in diatoms, similarly to Zx in vascular plants and green algae, is also bound to FCP complexes, inducing detachment and aggregation of the FCPs, which finally results in the formation of the quenching sites postulated by the recent nonphotochemical quenching (NPQ) models (Magdaong & Blankenship, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a previous study found that the reduced leaf photosynthesis upon sulfur treatment was due to non-stomatal limitation, as the reduction of photochemical reactions causes more energy to be dissipated as heat [13]. NPQ represent the response of the photosynthetic membrane to excess light intensity, it is crucial for balancing the energy distribution between growth and stress response by regulating photoinhibition and photoprotection [11,[21][22][23]. In the present study, the soil salinity pretreatment could induce PSI non-photochemical energy dissipation owing to the donor-side limitation and regulated energy dissipation in PSII, and maintained higher NPQ at PSII.…”
Section: Discussionmentioning
confidence: 91%